Use of Health Services by People With Dementia Who Self‐Harm in New South Wales, Australia: A Data Linkage Study - Adrian R. Walker; Preeyaporn Srasuebkul; Julian N. Trollor; Anne P. F. Wand; Brian Draper; Rachael C. Cvejic; Annette Moxey; Simone Reppermund (International Journal of Geriatric Psychiatry, 2026)
ABSTRACT Introduction This study aimed to examine the patterns and predictors of health service use for people with dementia who self‐harmed. Methods Using a retrospective linked cohort of people who accessed health services in New South Wales, Australia between 2001 and 2015, we identified 154,811 people with dementia or mild cognitive disorder (the dementia cohort), 28,972 people who self‐harmed (the self‐harm cohort), and 1541 who had a record of both dementia or mild cognitive disorder and self‐harm (the dementia and self‐harm subgroup). We examined the rates of health service use (inpatient hospital admissions, emergency department presentations, and mental health ambulatory days) for these cohorts. Using random effects Poisson regression and survival modelling, we investigated the change in and predictors of health service use following self‐harm (for those with dementia) or dementia diagnosis (for those who had self‐harmed). Results People with dementia who self‐harmed had the highest rate of use of all health services. Ambulatory mental health service use increased after self‐harm for people in the dementia cohort, while emergency department and mental health related hospital presentations decreased. Hospitalisations for non‐mental health reasons increased after dementia diagnosis for those in the self‐harm cohort, but use of other services decreased. Ambulatory mental health service use predicted increased time to re‐presentation to hospital. Discussion Health service use changed after an episode of self‐harm for people with dementia. People with dementia with poor mental health or substance use concerns may benefit from more proactive provision of mental health services.